The Restoration Movement of the Churches of Christ - Mladen Jovanović (Kairos (English Ed.))
The restoration of the church of Jesus Christ is a constant need and fact. The church is alive and everything living searches for continuous restoration. The Restoration Movement isn’t a short-lived movement. It began at the end of the 18th century and produced a large number of churches throughout the world that long for the return of authentic New Testament Christianity. Croatia’s familiarity with the Restoration Movement and its beginning, successes and legitimacy are the themes of this article.